Surface phenomena during the early stage of liquid phase SPS of a mixture of coarse WC and Ni‐alloy particles. (23rd March 2018) - Maizza, G.; Montanari, R.; Richetta, M.; Varone, A.; Kaciulis, S.; Mezzi, A.; Soltani, P.
Abstract : The tool industry strongly demands more economical, high‐performance, healthy, and ecological Co‐free WC‐based composites. Nickel is considered the optimal substitute of Co in WC‐based cermets to attain nearly comparable, if not superior properties in terms of wear resistance and fracture toughness. The combination of WC‐Ni with spark plasma sintering (SPS) process may represent a key factor to enhance the properties of future WC‐Ni composites. This work aims at studying the early stage of liquid phase sintering of a WC‐Ni‐alloy powder mixture made of coarse spheroidal WC (80 vol%) and Ni‐brazing alloy (20 vol%) particles during low pressure (16 MPa) pulsed SPS. Liquid phase phenomena were investigated both morphologically and analytically by energy dispersive X‐ray spectroscopy and X‐ray photoelectron spectroscopy. The results reveal that the interface reaction between the liquid Ni and WC particles causes the formation of an outer reaction shell within the WC particles, which is an Ni‐W solid solution. Most of necks originated between WC particles were favored by the presence of such reaction shell without any liquid interlayer. A relevant presence of graphitic carbon was observed over the surface of WC particles. The larger atomic W2 C/WC ratio in the initial WC powder decreased in the compact after SPS owing to the stabilization reaction between W2 C and carbon diffusing across the reaction shell.